2014
DOI: 10.1080/08351813.2014.958280
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia Sufferers’ Displays of Affect in Conversation

Abstract: How do people with aphasia express their emotions? This article uses a sample of video-recorded speech and language therapy sessions to see how patients make use of facial, vocal, and bodily expression. Analysis shows that their affect displays regularly co-occur with linguistic difficulties and efforts to repair them. The most common affect displays consist of frowning, laughing, smiling, and shifts in gaze or body posture. If the difficulties are prolonged, affect displays are intensified with lowered/raised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…For example, through applying Conversation Analysis, research has demonstrated that PWA use gaze for interaction management, such as turning gaze to the recipient to solicit assistance from the recipient (Damico, Oelschlaeger, & Simmons-Mackie, 1999;Goodwin & Goodwin, 1986;Wilkinson, 2007). Furthermore, PWA have been argued to use shifts in gaze to hold or yield a turn in conversation (Laakso, 2014). Such gaze practices, and also those of withdrawing gaze to display a word search as one's own, self-directed activity, are similar to those used by NBD communicators (e.g., Laakso, 1997).…”
Section: Speaker Gazementioning
confidence: 99%
See 3 more Smart Citations
“…For example, through applying Conversation Analysis, research has demonstrated that PWA use gaze for interaction management, such as turning gaze to the recipient to solicit assistance from the recipient (Damico, Oelschlaeger, & Simmons-Mackie, 1999;Goodwin & Goodwin, 1986;Wilkinson, 2007). Furthermore, PWA have been argued to use shifts in gaze to hold or yield a turn in conversation (Laakso, 2014). Such gaze practices, and also those of withdrawing gaze to display a word search as one's own, self-directed activity, are similar to those used by NBD communicators (e.g., Laakso, 1997).…”
Section: Speaker Gazementioning
confidence: 99%
“…Body posture is another topic that has received little attention in aphasia research. An exception to this is a study carried out by Laakso (2014), who examined how PWA display affect in conversation. She argues that shifts in body postures are one of the most common affect displays and that PWA use affect displays in close coordination with shifts in body posture that reflect turn organisation (Laakso, 2014).…”
Section: Body Posturementioning
confidence: 99%
See 2 more Smart Citations
“…In aphasia, much less research has been done on the influence of face and eye movements in conversation. In production, PWA have been shown to use facial movements in interaction to show emotions (Laakso, 2014a) and to indicate problems in conversation, such as with eyebrow movement, smiling and laughter (Laakso, 2014a;Kaukomaa et al, 2014). Goodwin (1995) (Preisig et al, 2015;Youse et al, 2004;Schmid & Ziegler, 2006).…”
Section: Face and Eye Movementsmentioning
confidence: 99%